Some perturbed inequalities of Ostrowski type for twice differentiable functions - Erden, Samet; Budak, H¨Useyin; Sarikaya, Mehmet Zeki; Erden, Samet (Publishing House of the Romanian Academy, 2021)
We establish new perturbed Ostrowski type inequalities for functions whose second derivatives are of bounded variation. In addition, we obtain some integral inequalities for absolutely continuous mappings. Finally, some inequalities related to Lipschitzian derivatives are given. © 2021 Elsevier B.V., All rights reserved.
Keywords: Function of Bounded Variation; Perturbed Ostrowski Type Inequalities